Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles - Azevedo, Letícia H.; Castilho, Raphael C.; Berto, Marielle M.; Moraes, Gilberto J. De (Zootaxa, 2017)
Macrochelid mites have been reported in several papers about mites of different habitats in Brazil, but this is the first work specifically conducted to determine the macrochelids from that country. The main goal was to determine macrochelid species in microhabitats where the stable fly is usually found in commercial cattle farms. In total, 1359 specimens were collected from cow manure and litter in different regions of São Paulo state. These represented ten species of three genera. One of these, Macrocheles embersoni n. sp. is here described as new to science. Other macrochelid species are expected to be found in the study area, when other types of microhabitats are explored.